Cannabis-Based Products in a Neurological Setting: A Clinical and Pharmacokinetic Survey - Mohamed, Susan; Lopane, Giovanna; Sabattini, Loredana; Scandellari, Cinzia; Zardi, Diletta; Donadio, Vincenzo; Rizzo, Giovanni; Perrone, Alessandro; Lugaresi, Alessandra; Contin, Manuela (Frontiers in Neurology, 2022)
Background and Aim Limited data are available in clinical settings on the pharmacokinetics of delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). We investigated the use of cannabis-based products in neurological practice, monitoring patients' steady-state cannabinoids (CBs) plasma concentrations matched with different preparations. Methods This was a prospective, single-center, observational study. Patients underwent venous blood withdrawal before the CBs' morning dose and then 2.5 h post-dosing. Spasticity or pain were patient self-assessed by the Numeric Rating Scale (NRS) before the morning CB's administration and 2.5 h post-dosing. Results Thirty-three patients were enrolled. Main indications for CBs were spasticity and chronic pain. Sixteen patients were treated with oromucosal spray formulation Sativex® and 17 with oil-based solutions. Both CBs trough plasma concentrations were ≤ limit of detection (0.1 ng/ml) in 45% of patients. Intrasubject CB's plasma levels significantly increased over baseline values in patients treated with Bediol® oil (p < 0.05) and Sativex® (p < 0.01). Post-dosing CB's bioavailability did not significantly differ between oral oil and oromucosal spray. NRS scores decreased (p < 0.01), matching the increase (p < 0.01) in CB's plasma concentrations. Conclusion This is the first study investigating CB's plasma concentrations of oral and oromucosal preparations in real-world neurological practice. Findings of similar bioavailability for both CBD and THC after galenic oil compared with oromucosal spray dosing may be clinically relevant and deserve additional research in larger cohorts.